2020
DOI: 10.17811/rifie.49.4.2020.429-438
|View full text |Cite
|
Sign up to set email alerts
|

Project-based learning in the classroom: a case study at High school level

Abstract: This research presents the results of a case study that analyses the Solidarity Atocha project, which was implemented at a school in Madrid, Spain, and in which 114 first-year High school students participated. The main objective of this study is to analyse the experience of students that participated in the Solidarity Atocha project and to understand how they evaluated it and how satisfied they were with it. The method applied in this case study is a mixed one that used both qualitative and quantitative techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…However, students perceive PBL to be time-consuming because of the increased workload and demands entailed by their efforts (Gómez-Pablos et al, 2020;Imaduddin et al, 2021). They mentioned the additional time they required to collaborate with classmates and complete projects, as well as the need to balance PBL tasks with exam preparation (Gómez-Pablos et al, 2020;Othman et al, 2022). Although PBL offers valuable learning experiences, it is essential to address student concerns regarding time management (Imaduddin et al, 2021).…”
Section: Students' Perceptions Of Project-based Learning In K-12 …mentioning
confidence: 99%
See 1 more Smart Citation
“…However, students perceive PBL to be time-consuming because of the increased workload and demands entailed by their efforts (Gómez-Pablos et al, 2020;Imaduddin et al, 2021). They mentioned the additional time they required to collaborate with classmates and complete projects, as well as the need to balance PBL tasks with exam preparation (Gómez-Pablos et al, 2020;Othman et al, 2022). Although PBL offers valuable learning experiences, it is essential to address student concerns regarding time management (Imaduddin et al, 2021).…”
Section: Students' Perceptions Of Project-based Learning In K-12 …mentioning
confidence: 99%
“…Gómez-Pablos et al (2020) revealed that many students felt lost and overwhelmed, particularly when confronted with new and unfamiliar projects. They expressed a need for guidance, highlighting the importance of providing scaffolding and mentorship in the PBL context.…”
mentioning
confidence: 99%